Genetic Map of Mango: A Tool for Mango Breeding - Kuhn, David N.; Bally, Ian S. E.; Dillon, Natalie L.; Innes, David; Groh, Amy M.; Rahaman, Jordon; Ophir, Ron; Cohen, Yuval; Sherman, Amir (Frontiers in Plant Science, 2017)
Mango (Mangifera indica) is an economically and nutritionally important tropical/subtropical tree fruit crop. Most of the current commercial cultivars are selections rather than the products of breeding programs. To improve the efficiency of mango breeding, molecular markers have been used to create a consensus genetic map that identifies all 20 linkage groups in seven mapping populations. Polyembryony is an important mango trait, used for clonal propagation of cultivars and rootstocks. In polyembryonic mango cultivars, in addition to a zygotic embryo, several apomictic embryos develop from maternal tissue surrounding the fertilized egg cell. This trait has been associated with linkage group 8 in our consensus genetic map and has been validated in two of the seven mapping populations. In addition, we have observed a significant association between trait and single nucleotide polymorphism (SNP) markers for the vegetative trait of branch habit and the fruit traits of bloom, ground skin color, blush intensity, beak shape, and pulp color.